Status and prospects of anode materials for efficient electrochemical ozone production - Xiuyue Wang; Ye Yuan; Zheyuan Ding; Junna Yang; Yilin Wang; Siming Li; Yu Ding; Yawei Li; Min Wang; Mingbo Wu (Energy Reviews)
Utilizing efficient and eco-friendly electrochemical techniques for the synthesis of valuable chemicals represents an optimal strategy for enhancing energy utilization. Electrochemical ozone production (EOP), recognized for its cleanliness and adaptability, emerges as a promising energy conversion technology for the synthesis of high-value chemicals. However, the selection of anode materials poses a significant challenge to the widespread commercial deployment of EOP, and a thorough investigation into this area is crucial for improving both the performance and durability. In this review, we delve into the fundamental principle of ozone generation, explore the advantages and constraints associated with various EOP systems, and discuss how the utilization of advanced membrane electrode assembly (MEA) electrolysis cells can sustain an overall efficiency of 20 ​% or higher. This review offers objective evaluations of various anode materials and summarizes recent advancements in EOP, highlighting laboratory-measured current efficiencies that surpass 50 ​%. Lastly, this review delineates the myriad challenges encountered within the current EOP research and proposes potential avenues for future development, all in an effort to furnish indispensable insights for the industrial implementation of EOP.